Avaliação do potencial de utilização dos resíduos da poda e corte de arbóreos e gramíneas (massa verde) na geração de energia térmica - Santos, Mayer Andrade (2019)
In this work the possibility of using biomass residues from tree prunings and cuttings, and grazing of grasses (green mass), as a possible fuel to be used in thermoelectric power plants. These residues were characterized in terms of composition (Lignin, Cellulose / hemicellulose, Moisture content, Ash content, Organic matter content, Carbon content (TOC), thermal analysis (TG, DTA and DSC) and calorific content (Heat of combustion). The water present in the material is the main impediment of using this biomass as fuel, containing about 10% in the chip and 7% in the grasses. The heat of combustion of the material was 4,048 kcal/kg for the grasses and 4,397 kcal/kg for the chip. The greater amount of lignin in the chip, 32% against 25% in the grasses, explains this difference. Our results show the possibility of using that biomasses as fuel in thermoelectric plants in times of water crisis, when the possibility of almost complete drying of the material is feasible, using only natural insolation.